From Existential Vacuum to Thriving: Meaning-Centered Group Interventions for University Students - Fika Dwi Mulia; Neviyarni Neviyarni; Netrawati Netrawati; Rezki Hariko (Universitas Negeri Padang, 2025)
University students frequently experience existential concerns alongside subclinical psychological distress, including reduced meaning in life, depression, and anxiety. Meaning-centered group counseling based on logotherapy has been proposed as a preventive intervention; however, evidence for young adult populations remains limited. This study employed a Systematic Literature Review with Network Analysis (SLNA) conducted in accordance with the PRISMA 2020 guidelines to examine the effectiveness and research landscape of meaning-centered group counseling for university students. A systematic search of the Scopus database (2015-2025) identified five controlled studies (N = 206) involving group-based logotherapy interventions for individuals aged 18-25 years. Meaning in life was the primary outcome, while depression, anxiety, and stress were secondary outcomes. Due to heterogeneity, data were synthesized using SWiM guidelines and complemented by a bibliometric keyword co-occurrence analysis of 47 Scopus-indexed articles using VOSviewer. The results indicate consistent and significant improvements in meaning in life (p < 0.05) with large effect sizes, accompanied by reductions in psychological distress. These findings support meaning-centered group counseling as an effective preventive intervention in university counseling settings.